Shamed If You Do, Shamed If You Do Not: Group-Based Moral Emotions, Accountability, and Tolerance of Enemy Collateral Casualties - Schori-Eyal, Noa; Sobol-Sarag, Danit; Shuman, Eric; Halperin, Eran (Frontiers in Psychology, 2022)
Civilian casualties contribute to the perpetuation of intergroup conflicts through increased radicalization and hostilities, but little is known on the psychological processes that affect responses to outgroup civilian casualties. The goal of the present research was to explore two factors expected to lead group members to act more cautiously, thereby reducing civilian casualties: perceived accountability and forecast group-based moral emotions. In two studies, Jewish-Israeli civilians (Study 1) and soldiers (Study 2) were asked to forecast their group-based moral emotions in case of Palestinian (i.e., outgroup) civilian casualties, then exposed to accountability manipulations. Participants who expected to feel low levels of shame and were primed with accountability made more cautious decisions than those in the control condition. Participants who expected to feel high levels of shame were unaffected by accountability primes. Theoretical and practical implications regarding forecast moral emotions and accountability as an intervention in intergroup conflicts are discussed.